The Role of Resistin in Patients with Primary Fibromyalgia - Alosami, Mohammed H. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Fibromyalgia syndrome (FMS) is a common rheumatologic syndrome with multiple manifestations and associated with many diseases, it characterized by chronic widespread muscular pain and tenderness. Resistin is an adipokine discovered in 2001 and considered as a link between obesity and type 2 diabetes by antagonizing and resisting theaction of insulin as it name encompass ;resistin (resist insulin) . It is secreted mainly from adipose tissue in mice and from white blood cells besides the adipose tissue in humans.Research reviled that resistin has a role in some inflammatory diseases like Rheumatoid Arthritis (RA).Objective: The objective of this study is to measure Resistin concentration and to evaluate its role in the pathogenesis of primary FMS.Patients and methods: Fifty patients with primary FMS were included in this study (37 females and 13 males) the age range of (17-65) years (Mean ± SD) (40.13 ± 12.0) years, andthirty healthy individuals volunteers (21 females and 9 males), whose age and sex matching with FMS patients, age ranging (18 - 63) years, (Mean ± SD) (36.1 ±10.0) years. Resistinconcentration was measured in sera of patients and controls by ELISA kit. Anthropometric measurements like body mass index (BMI) and waist circumference (WCr) were taken, besidesother features like sleep disturbance, emotional distress, and fatigue were reported.Results: Resistin concentration was higher in FMS patients than controls (2.15±0.9) ng /ml vs. (1.57±0.6) ng /ml. This elevation was highly significant statistically (p=0.003).Othermeasurements in patients group like BMI, WCr were (28.39±5.0) Kg/m2 and (100.34±13.21) cm respectively .These values were highly significant when compared to their control group(p=0.002) and (p=0.008) respectively . Serum resistin level was positively correlated with both waist circumference (r=0.411,p=0.003) and age (r=0.405 ,p=0.004) . Waist circumference waspositively correlated with age (r=0.604, p=0.000).Clinical features like sleep disturbance, emotional distress ,and fatigue showed highly significant difference between the two groups .No significant differences were reported with respect to age and sex.Conclusion: The result of the current study suggest that Resistin might have a role in the pathogenesis of FMS.